Age-related changes in attentional control across adolescence: how does this impact emotion regulation capacities? - Cohen Kadosh, Kathrin; Heathcote, Lauren C.; Lau, Jennifer Y. (Frontiers in Psychology, 2014)
This study set out to establish the use of a novel task, the go/no-go Overlap task, for investigating the role of attentional control capacities in the processing of emotional expressions across different age-groups within adolescence: at the onset of adolescence (11-12 year-olds) and towards the end of adolescence (17-18 year-olds). We also looked at how attentional control in the processing of fearful, happy, and neutral expressions relates to individual differences in trait anxiety in these adolescent groups. We were able to show that younger adolescents, but not older adolescents had more difficulties with attention control in the presence of all faces, but particularly in the presence of fearful faces. Moreover, we found that across all groups, adolescents with higher trait anxiety exhibited attentional avoidance of all faces, which facilitated relatively better performance on the primary task. These differences in reaction time emerged in the context of comparable accuracy level in the primary task across age-groups. Our results contribute to our understanding of how attentional control abilities to faces but in particular fearful expressions may mature across adolescence. This may affect learning about the environment and the acquisition of behavioural response patterns in the social world.